2020
DOI: 10.1007/s10584-020-02831-1
|View full text |Cite
|
Sign up to set email alerts
|

Adapting cultural heritage to climate change impacts in the Netherlands: barriers, interdependencies, and strategies for overcoming them

Abstract: Climate change is currently impacting cultural heritage globally. Despite advances in the understanding of the relationship between climate change impacts and cultural heritage, there are significant barriers that hamper adaptation of cultural heritage to current and projected climate risks. This paper aims to advance the empirical understanding of barriers to adapting cultural heritage to climate-related impacts in the Netherlands by identifying different barriers, their interdependencies, and possible strate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(39 citation statements)
references
References 52 publications
(91 reference statements)
1
32
0
Order By: Relevance
“…These findings might be associated with the Netherlands' efforts for realizing its ambitious Sustainability Agenda that included, for instance, "the Dutch Dairy Organisation and the Dutch Agricultural and Horticultural organisation to have zero-carbon emissions in dairy chains by 2020" through green practices [60]. The Netherlands is one of the most prominent examples of European countries recognizing the urgent need for the implementation of green practices in order to protect also the CH of the country [19][20][21]. It is not surprising that 26 countries in Europe (see Figure 3) are represented in the study's sample.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings might be associated with the Netherlands' efforts for realizing its ambitious Sustainability Agenda that included, for instance, "the Dutch Dairy Organisation and the Dutch Agricultural and Horticultural organisation to have zero-carbon emissions in dairy chains by 2020" through green practices [60]. The Netherlands is one of the most prominent examples of European countries recognizing the urgent need for the implementation of green practices in order to protect also the CH of the country [19][20][21]. It is not surprising that 26 countries in Europe (see Figure 3) are represented in the study's sample.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it must be tackled to protect the Netherlands' CH. At this point, it should be mentioned that climate change has challenged the CH management approaches globally, as they seek to deal effectively with the threats caused by the environmental change by promoting sustainable models [21].…”
Section: Communication Cultural Heritage and Green Hostingmentioning
confidence: 99%
“…All interviewees stated, in one form or another, that the CH program at their organisation was too old to include climate threats and it is clear that the identi cation of threats to CH has just begun at the organisations included in this study. A national strategy for climate change orientated CH and landscape planning also appears to be lacking, and, moreover, there are currently no clear routines for prioritisation, a problem highlighted as a barrier to planning (Uittenbroek, 2016;Fatorić and Biesbroek, 2020). This applies to all of the administrative levels studied, with almost all climate related work being undertaken reactively and competing for time with existing tasks which are required by legislation.…”
Section: Discussionmentioning
confidence: 99%
“…Su cient resources, both monetary and personnel, are barriers to a smooth planning process (Bedsworth and Hanak 2013;Ziervogel and Parnell, 2014). However, Fatorić and Biesbroek (2020) found that institutional and technical barriers dominated over nancial barriers in the Netherlands. Granberg and Elander (2007:546) touched upon a possible reason for the perceived lack of resources, raising the more general question of how municipalities prioritise with respect to territory and citizens, and "not just particular categories" in which some actions are executed at the expense of others.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation